Doyle–Kirmse Reaction of S-Allyl and S-Propargyl Phosphorothioates - Tual, Laurine; Rognan, Charlou; Maujean, Timothé; Pertschi, Romain; Girard, Nicolas; Blond, Gaëlle; Gulea, Mihaela (Synthesis, 2025)
The Doyle–Kirmse reaction represents a powerful synthetic tool for forming both C–S and C–C bonds in a single process. The rhodium-catalyzed Doyle–Kirmse reaction of S-allyl and S-propargyl phosphorothioates with diazoesters has been developed and represents a rare example involving substrates bearing an electron-withdrawing group on the sulfur atom. The transformation takes place at room temperature, in only 5 minutes, and leads via a [2,3]-sigmatropic rearrangement of the sulfonium ylide intermediate to the corresponding S-homoallyl or S-homoallenyl phosphorothioates in yields ranging from 25% to 92% (19 examples).
Keywords: Doyle–Kirmse reaction; [2,3]-rearrangement; propargyl sulfides; allyl sulfides; diazoesters; phosphorothioates; C–S bond formation